Knowledge and certainty about medication administration among nursing students in University Malaysia Sabah - Chong, Li Tsu; Josephine Magdeline Joseph; Nur Atikah Mohd Taib; Nurfirna Suzleyna Mohd Salleh; Jennefer Henry (Malaysian Journal of Medicine and Health Sciences, 2020)
Medication error always happens among the nurses either the trained out staffs nor in nursing students. These errors may harm any patient that is involved and it may lead tolegislation issue. Therefore, this study aims to identify nursing students knowledge and assurance in medication administration. Methods: This study using a cross-sectional survey design using a convenience sampling method. Ethical approval was obtained from The Fac¬ulty of Medicine and Health Sciences Ethical Committee. Adapted questionnaire divided into three sections with 14 multi-choice questions for each section (pharmacology, drug management and drug calculation) score (0-14) and Self perceived certainty on their correct answer were scored (1-high certainty, 2-moderate and 3-low certainty). Questionnaires were distributed through the online google form to Diploma of Nursing students of year two and three of Faculty Medicine and Health Science of University Malaysia Sabah. Result reported in mean (+SD). Results: Total of71 students volunteered responded to the survey. 42.3% of respondents (n=30) are the Year Two students and 57.7% (n=41) are the Year Three students.In knowledge about pharmacology mean score was 9.33 (2.37) and their certainty mean score was 1.9 (0.55), Drug management mean score was 8.42 (2.55) and their certainty mean score was 1.90 (0.45), While for their drug calculation mean score was 8.04 (3.03) and certainty mean score was 2.13 (0.51). Conclusion: Knowledge in drug management and drug calculation both were below the appropriate score (less than 9) respectively. These indicate that more practices and training on the medication administration should be done to the students in order familiar with the context of medication administration. Their certainty level found moderate indicate that their confidence level on medication administration should be reinforced. Nursing educators need to facilitate the students in their learning process and training periods to gain their confidence before their graduation.